Meštrović a retrospective : Klovićevi Dvori Gallery - Vugrinec, Petra; Vujanović, Barbara 1983- (Klovićevi Dvori Gallery, 2023)
Catalog of an exhibition organized by Galerija Klovićevi dvori and Muzeji Ivana Meštrovića and held at Galerija Klovićevi dvori, Zagreb, Croatia, November 22, 2023 - March 3, 2024